2016
DOI: 10.1371/journal.pone.0147124
|View full text |Cite
|
Sign up to set email alerts
|

A Microarray-Based Analysis Reveals that a Short Photoperiod Promotes Hair Growth in the Arbas Cashmere Goat

Abstract: Many animals exhibit different behaviors in different seasons. The photoperiod can have effects on migration, breeding, fur growth, and other processes. The cyclic growth of the fur and feathers of some species of mammals and birds, respectively, is stimulated by the photoperiod as a result of hormone-dependent regulation of the nervous system. To further examine this phenomenon, we evaluated the Arbas Cashmere goat (Capra hircus), a species that is often used in this type of research. The goats were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 47 publications
(44 reference statements)
4
33
0
Order By: Relevance
“…1 ). Because the duration and definition of proanagen (early anagen) have been debated 16 , 17 , we estimated that the timing of the transition from early anagen to the anagen phase was between June and August, which is consistent with the results of the study by Liu et al . 17 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…1 ). Because the duration and definition of proanagen (early anagen) have been debated 16 , 17 , we estimated that the timing of the transition from early anagen to the anagen phase was between June and August, which is consistent with the results of the study by Liu et al . 17 .…”
Section: Discussionsupporting
confidence: 88%
“…Cashmere is derived from secondary hair follicles (SHFs) which are distinct from primary HFs (PHFs) in both their morphogenesis and transcriptome profiles 15 . Limited publications have shown that SHFs likely go through proanagen (early anagen), anagen, catagen and telogen 16 , 17 , although the definition of proanagen is not fully clear in Cashmere goat. It is believed that SHF cycling receives continuous stimulation from external signals (photoperiod) and that it is regulated by a series of key regulatory factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of differences between the breed, heredity and living environment of domestic animals, our molecular and morphological understanding of hair follicle biology relies a great deal on mouse hair follicle research. In recent years, studies on Cashmere goat hair follicles has increased [27][28][29], providing valuable information for further research on the molecular mechanisms associated with these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to improve the quality of cashmere, the fineness of cashmere has become more and more popular (Bai et al, 2016;Zhang et al, 2018). Investigations indicated that many genes might widely participate in the growth regulation of cashmere fiber (Stenn and Paus, 2001;Liu et al, 2016). Many studies have identified some genes associated with the growth and properties of wool fibers in sheep and goats, such as DSG1, IGF-IR, KRTAPs, ILK, as well as the KRT and KRTAP genes (Rufaut et al, 1999;Bin et al, 2006;Yu et al, 2011;Yang et al, 2012;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%